2004
DOI: 10.1094/pdis.2004.88.12.1352
|View full text |Cite
|
Sign up to set email alerts
|

Impact of White Mold Incidence on Dry Bean Yield Under Nonirrigated Conditions

Abstract: Studies on chemical control of white mold, conducted between 1994 and 2001 at several locations in North Dakota, resulted in diverse levels of white mold incidence and severity. Navy bean cultivars were evaluated in on-farm trials between 1994 and 1996, while pinto bean cultivars were used between 1997 and 2001. The relationship between yield and white mold incidence in these trials was examined using correlation and regression analysis. White mold incidence was correlated to severity using a second-degree pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Due to the lack of adequate levels of host resistance, fungicides have been a major control method for Sclerotinia diseases (Bardin and Huang, 2001;Steadman, 1979). Fungicides have been used successfully on a commercial scale with soybean, dry bean, oilseed rape and some vegetables (Bailey et al, 2000;Budge and Whipps, 2001;Del Rio et al, 2004;Twengstrom et al, 1998), although the development of resistance to fungicides is always a threat (Gossen et al, 2001). Additionally, control can be inconsistent due to difficulties in achieving good spray coverage and correlating application with the release of ascospores.…”
Section: Disease Controlmentioning
confidence: 99%
“…Due to the lack of adequate levels of host resistance, fungicides have been a major control method for Sclerotinia diseases (Bardin and Huang, 2001;Steadman, 1979). Fungicides have been used successfully on a commercial scale with soybean, dry bean, oilseed rape and some vegetables (Bailey et al, 2000;Budge and Whipps, 2001;Del Rio et al, 2004;Twengstrom et al, 1998), although the development of resistance to fungicides is always a threat (Gossen et al, 2001). Additionally, control can be inconsistent due to difficulties in achieving good spray coverage and correlating application with the release of ascospores.…”
Section: Disease Controlmentioning
confidence: 99%
“…Adequate control of white mold using fungicides, biopesticides (e.g., Coniothyrium minitans, Gliocladium virens, Sporidesmium sclerotivorum, Trichoderma viride), and other disease management strategies has been difficult (Agrios, 2005;del Río et al, 2004;Schwartz and Steadman, 1989;Steadman and Boland, 2005), especially on the susceptible indeterminate prostrate growth habit Type III (Singh, 1982b) common bean cultivars that have traditionally predominated in the western United States. However, (i) direct intact or live plants, (ii) direct detached plant organs, and (iii) indirect approaches.…”
Section: The Fungus Sclerotinia Sclerotiorum and Pathogenic Variabilitymentioning
confidence: 99%
“…The screening methods used were (i) placing a mycelial plug on cotyledons, (ii) the cut-stem method, and (iii) inoculating detached leaves with a mycelial suspension. The cut-stem method was the most efficient timing of fungicide applications between 50 and 100% bloom did significantly reduce white mold severity and yield loss for upright indeterminate navy and pinto bean grown under nonirrigated (del Río et al, 2004) and sprinkler irrigated (Schwartz et al, , 1994 production systems. They also reported that net returns to producers were increased up to US$260 ha -1 with low to moderate disease pressure and low market values for pinto bean.…”
Section: The Fungus Sclerotinia Sclerotiorum and Pathogenic Variabilitymentioning
confidence: 99%
“…de Bary, is a devastating disease that limits yield potential (Del Río et al 2004;Singh and Schwartz 2010) and reduces seed and pod quality. The disease is widespread, occurring across major bean production regions of North and South America, and Europe (Schwartz and Steadman 1989).…”
Section: Introductionmentioning
confidence: 99%